Products for the treatment of inflammatory bowel disease: a patent review (2013-2014) - Di Stasi, Luiz C. [UNESP]; Costa, Celso A. R. A. [UNESP]; Witaicenis, Aline [UNESP] (Informa Healthcare, 2015)
Introduction: Inflammatory bowel disease (IBD) consists of Crohn's disease, ulcerative colitis and an unspecific IBD. The unclear etiology of IBD is a limiting factor that complicates the development of new pharmacological treatments and explains the high frequency of refractory patients to current drugs, including both conventional and biological therapies. In view of this, recent progress on the development of novel patented products to treat IBD was reviewed.Areas covered: Evaluation of the patent literature during the period 2013 - 2014 focused on chemical compounds, functional foods and biological therapy useful for the treatment of IBD.Expert opinion: Majority of the patents are not conclusive because they were based on data from unspecific methods not related to intestinal inflammation and, when related to IBD models, few biochemical and molecular evaluations that could be corroborating their use in human IBD were presented. On the other hand, methods and strategies using new formulations of conventional drugs, guanylyl cyclase C peptide agonists, compounds that influence anti-adhesion molecules, mAbs anti-type I interferons and anti-integrin, oligonucleotide antisense Smad7, growth factor neuregulin 4 and functional foods, particularly fermented wheat germ with Saccharomyces cerevisiae, are promising products for use in the very near future.
Keywords: Colitis; Crohn’s disease; Functional foods; Inflammatory bowel disease; Intestinal anti-inflammatory compounds; mAb; Natural products; Rebiotic; Probiotic